Additive Adsorption on DLC Coatings in Static and Tribological Conditions Using Neutron Reflectometry - Čoga, Lucija; Simič, Rok; Geue, Thomas; Kalin, Mitjan (Frontiers in Mechanical Engineering, 2019)
Neutron reflectometry (NR) has proven to be an important analytical tool for investigations of the adsorption in boundary lubrication for both simple and complex additives by using either deuterated additives or the base carrier lubricant. NR enables in-situ measurements of the adsorption during surface exposure to additivated lubricants, and at the same time provides quantitative parameters for the adsorbed layer with sub-nanometre precision. In this work, NR was successfully used to determine the thickness and the density of the adsorbed layers of various lubricating additives (oiliness additives and ZDDP) on different DLC coatings. First, the influence of the coating structure and the presence of the doping element on the adsorption of two simple oiliness additives, i.e., hexadecanol and hexadecanoic acid, are presented. Second, the interaction ability of the ZDDP additive on a hydrogenated DLC (a-C:H) coating was measured as a function of the temperature and exposure time. Finally, an in-house-developed tribological rig was implemented in the neutron beam reflectometer to investigate the ZDDP film’s growth and removal. The results show the unique ability of NR to provide direct evidence of the adsorption of additives on DLC coatings as a function of several relevant engineering parameters, such as time, temperature and rubbing.